IDENTIFICATION OF FACTORS INFLUENCING EMPLOYEE WORK PRODUCTIVITY IN OIL PALM PLANTATIONS - Pulungan, Delyana R.; Roosmawati, Febriana; Widjajanto, Adi; Hasibuan, Muhammad Rizky Adhitya; Sipayung, Antonio M.; rasyid, MHD. Andi (CERED Indonesia Institute, 2025)
Work productivity is a comparison between the results achieved and employee participation per unit of time. Age has an influence on labor productivity. A person's length of service has an influence on their work. The study was conducted in Afdeling 2, Afdeling 4 and Afdeling 5 during the period March - May 2024. The purpose of this study was to identify factors that influence the work productivity of harvest employees in oil palm plantations using quantitative descriptive research methods. The results of the study indicate a positive and significant influence of age and work experience on the Work Productivity of harvest employees in PT.X plantations Based on Multiple Linear Regression Analysis Y = 24.034 + 0.228X1 + 0.231X2. Based on the results of the hypothesis test, the results are the calculated t value of the Age variable (X1) 4.132 > 1.987 t table value and significant value 0.000 < 0.05 meaning that the Age variable (X1) has an effect on the variable Work productivity of harvest employees (Y), the calculated t value of the Work Experience variable (X2) 3.815 > 1.987 t table value and significant value 0.000 < 0.05 meaning that the Work Experience variable (X2) has an effect on the variable Work productivity of harvest employees (Y). The results of the determination test are 36.5%.